Discurso político, ethos e memória discursiva: uma análise da constituição do sujeito Lula - Baviera, Evaldo (2008)
Taking as theoretical reference the analysis of speech based on a French line, coming from its fountain – Michel Pêcheux and Michel Foucault – but also other contemporary researchers such as Gregolin, Charaudeau e Maingueneau, we tried in this work to reflect the political speech; the discoursive memory and ethos. We elect as corpora the president Luiz Inacio Lula da Silva ´s possession speech in 2003 and some charges that occurred in that occasion of his involvement with corruption episodes in 2005. We tried to verify how is the construction of subject Lula in a speech typically political - an ethos that brings enthusiasm and a transformation and how a new political happening interferes in the reconstruction or desconstruction of this subject. In this way we tried to show the similiarities and differences and which effects of meaning are produced in these two moments of political course of Lula. Key words: political speech, ethos, discoursive memory, Lula.